High Prevalence and Endemism of Trypanosomatids on a Small Caribbean Island - Votýpka, Jan; Kment, Petr; Kriegová, Eva; Vermeij, Mark J A; Keeling, Patrick J; Yurchenko, Vyacheslav; Lukeš, Julius (The Journal of eukaryotic microbiology, 2019)
We describe the monoxenous trypanosomatids parasitizing true bugs and flies on the island of Curaçao. Out of 248 examined true bugs belonging to 17 species, 93 individuals were found to be infected (overall 38% prevalence) by at least one trypanosomatid species (referred to as typing units; TUs). Out of 80 flies, six were infected. All detected trypanosomatids were compared based on their 18S rRNA sequences with TUs parasitizing bugs and flies described from mainland South America, allowing us to assess their diversity and distribution. Besides Leptomonas pyrrhocoris and Leptomonas seymouri, two known species of the subfamily Leishmaniinae, our analysis revealed six new TUs falling into the groups 'jaculum', Blastocrithidia and Herpetomonas. Moreover, two new members of the genus Phytomonas and three new TUs belonging to the monophyletic group designated as 'new clade II' sensu Mol. Phylogenet. Evol, 69, 255 (2013) were isolated. The detected trypanosomatids were characterized by moderate diversity (13 TUs) species richness. Out of nine and four TUs from the heteropteran and dipteran hosts, respectively, 11 TUs have not been encountered before. Although a sampling bias may partially affect the comparison between trypanosomatid communities on Curaçao and the mainland, the high proportion of unique TUs from the former location suggests that the prominent role of islands in increasing the global diversity of macroscopic organisms may also extend to their protistan parasites.
Keywords: endemic species; island biogeography theory; fylogeneze; RNA, Ribosomal, 18S; Phylogeny; Phytomonas; conservation; RNA, Protozoan; Trypanosomatina; Animals; evolution; zvířata; Curacao; RNA protozoální; Blastocrithidia; RNA ribozomální 18S; Diptera; Heteroptera; Leptomonas